The 1958 New York Convention in action - Paulsson, Marike (Kluwer Law International B.V., 2016)
"By drawing on the Convention?s drafting history in great detail, the book presents a coherent account of how the most frequently recurring interrogations about the text are reflected (or not) in judicial practice. The author studied more than 1,700 decisions rendered under the Convention since its inception in 1958 in order to provide a succinct selection of landmark cases per article. With its intense investigation of the complex reality underlying contracting States? commitment in principle and judicial application in fact, the author?s judicial understanding of the Convention provides a clear conceptual framework that will help avoid outcomes at odds with the purposes of this important instrument. Lawyers and judges will rely on this book not only to situate the Convention in the national legal orders where it is intended to produce its effects, but also discover practical ways to respond to distinct questions of application."--Publisher's website.